Hydroxyapatite electro discharge coating of Zr-based bulk metallic glass for potential orthopedic application - Aliyu, A.A. (Trans Tech Publications Ltd, 2019)
In the past, Electro Discharge Machining (EDM) process was well known in cutting extremely hard materials and fabricating complex shapes. Recently, EDM process has been hybridized to not only shape, but also coats the surface of workpiece material. In this study, the deposition of hard carbide and calcium-based oxides on the Zr-based bulk metallic glass (BMG) using hydroxyapatite mixed electro discharge coating (HAm-EDC) have been investigated. The aim is to enhance the biocompatibility and cell adhesion of the BMG as a potential implant. The chemical composition, morphology and thickness of the coated surface were characterized through Optical Microscope, Scanning Electron Microscopy (SEM), X-ray Spectroscopy (EDS) and X-ray Diffraction (XRD). Major hydroxyapatite elemental composition (Ca, P, O), carbides (ZrC, TiC) and oxides (ZrO, CaZrO3) were formed on the treated BMG surface. A coating of about 23 Âµm thick was achieved. The addition of hydroxyapatite powder in the dielectric fluid enhances the Zr-based BMG surface quality by reducing the surface cracks and the crater size. Â© 2019 Trans Tech Publications, Switzerland